Naringin attenuates inflammatory injury to the bovine endometrium by regulating the endoplasmic reticulum stress–PI3K/AKT–autophagy axis - Lu, Zihao; Peng, Qingyang; Hu, Ruiting; Wang, Yan; Fan, Kewei; Zhang, Tao (Frontiers in Pharmacology, 2024)
Background: Endometritis seriously affects maternal reproductive health and fertility. Natural compounds have the characteristics of high efficiency and low residue in disease treatment. We aimed to discover and reveal the pharmacological effects of naringin, which is widely present in food and plants, on endometritis. Methods: Based on network pharmacology, the potential targets and pathways of naringin’s actions on endometritis were predicted. Animal in vivo experiments were conducted to examine the inflammatory response of lipopolysaccharides (LPSs) in uterine tissue and the therapeutic effect of naringin. An in vitro primary bovine endometrial epithelial cell inflammation and drug treatment model was constructed. The production of reactive oxygen species (ROS) was measured using DCFH-DA, and the effect of naringin on LPS-induced endometritis was evaluated using HE staining, real-time quantitative PCR, Western blot, and immunofluorescence staining methods. Results: Naringin alleviated LPS-induced inflammatory injury and oxidative stress in the endometrium of mice and bovine endometrial epithelial cells (bEECs). Furthermore, in vitro studies were carried out to reveal the potential anti-inflammatory mechanisms of naringin based on network pharmacology. We found that naringin significantly inhibited LPS-stimulated endoplasmic reticulum stress (ERS)-related gene and protein expression, thus reducing the unfolded protein response (UPR). Furthermore, treatment of naringin attenuated the autophagic flux induced by ERS. In a further study, we observed that PI3K/AKT pathway inhibitors or ERS inducers partially reverse naringin’s inhibition of autophagy and cell apoptosis. Conclusion: It is demonstrated that naringin suppresses autophagy by directly inhibiting the ERS-PI3K/AKT axis and exerting anti-inflammatory and antioxidant effects in endometritis. These findings provide novel insights into the pathogenesis of endometritis, highlighting potential therapeutic targets of traditional herbs and compounds.